Impacts of Pesticides on Agriculture: Exploring the Effects of Pesticide Use on Agriculture and the Environment (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Pesticides are a category of chemicals used to eradicate an infestation or prevent furtherreproduction. Pesticides are often used to manage weeds or insect invasion in agricultural areas as wellas other pests and disease-carrying insects in homes, workplaces, shopping malls, and on publichighways. Pesticides' modes of action are not species-specific, therefore concerns have beenexpressed regarding the environmental harm associated with their exposure in many ways. Pesticidesof all kinds have been used for crop protection for hundreds of years. Although pesticides benefitcrops, they can have a harmful impact on the environment. Damage to biodiversity might result fromoveruse of pesticides. Injurious chemicals pose a threat to the survival of many aquatic creatures andbirds. Pesticides may enter the body by oral, inhalation, or dermal exposure, and it is generallyrecognized that they are the primary cause of a number of illnesses include respiratory conditions,cancer, skin issues, endocrine disruption, and infertility.